From Identity Verification to Behavior Prediction: Ethical Implications of Second Generation Biometrics - Sutrop, Margit; Laas-Mikko, Katrin (The Review of policy research, 2012)
In this article, we will compare ethical issues raised by first and second generation biometrics. First generation biometrics use characteristics readily visible to the naked eye to ensure that the person identified is the person he claims to be, whereas second generation biometrics focus on behavioral patterns with the aim of predicting suspicious behavior or hostile intentions. While the collection of biometric features for identification is visible to the person involved, capturing biometric features from a distance may go unnoticed. Our study of a range of U.S. and European projects of second generation biometrics, particularly of Future Attribute Screening Technology and Automatic Detection of Abnormal Behaviour and Threats in crowded Spaces, shows that if data subjects are not aware of the processing of their data, and if behavioral patterns are interpreted without any knowledge of the subject's will and motives, there are risks of discrimination and stigmatization. Thus, second generation biometrics raise some new ethical concerns besides issues of integrity, privacy, and data protection and further underscore the importance of the principle of informed consent in order to maintain public trust.